International Ship and Offshore Structures Congress 2018 - Michailides, Constantine (My University, 2026)
Member of the Committee ‘Specialist Committee V.2 Experimental Methods’ of the scientific organization, ISSC for the Congress ISSC2018. (National Correspondent)